Comparative Analysis of PCR–Electrospray Ionization/Mass Spectrometry (MS) and MALDI-TOF/MS for the Identification of Bacteria and Yeast from Positive Blood Culture Bottles - Kaleta, Erin J; Clark, Andrew E; Cherkaoui, Abdessalam; Wysocki, Vicki H; Ingram, Elizabeth L; Schrenzel, Jacques; Wolk, Donna M (Clinical chemistry (Baltimore, Md.), 2011)
Emerging technologies for rapid identification of microbes demonstrate a shift from traditional biochemical and molecular testing algorithms toward methods using mass spectrometry (MS) for the semiquantitative analysis of microbial proteins and genetic elements. This study was performed to assess the diagnostic accuracy of 2 such technologies, PCR-electrospray ionization (ESI)/MS and MALDI-TOF/MS, with respect to phenotypic and biochemical profiling as a reference standard method. A positive challenge set of blood culture bottles was used to compare PCR-ESI/MS and MALDI-TOF/MS performance on a matched set of samples. We performed characterization of bloodstream infections from blood cultures using the Ibis T5000 PCR-ESI/MS and the Bruker MALDI Biotyper 2.0 (MALDI-TOF/MS) platforms for microbial identification. Diagnostic accuracy was determined by independent comparison of each method to phenotypic and biochemical characterization with Vitek2 analysis as the reference standard identification. The diagnostic accuracy, represented as positive agreement, at the genus level was 0.965 (0.930-0.984) for PCR-ESI/MS and 0.969 (0.935-0.987) for MALDI-TOF/MS, and at the species level was 0.952 (0.912-0.974) with PCR-ESI/MS and 0.943 (0.902-0.968) for MALDI-TOF/MS. No statistically significant difference was found between PCR-ESI/MS and MALDI-TOF/MS in the ability to rapidly identify microorganisms isolated from blood culture. Our results demonstrate that PCR-ESI/MS and MALDI-TOF/MS are equivalent in their ability to characterize bloodstream infections with respect to the reference standard, and highlight key differences in the methods that allow for each method to have a unique niche as a tool for rapid identification of microbes in blood cultures.